2017
DOI: 10.1093/heapro/dax028
|View full text |Cite
|
Sign up to set email alerts
|

Improving health literacy through adult basic education in Australia

Abstract: Adults with low literacy are less empowered to take care of their health, have poorer health outcomes and higher healthcare costs. We facilitated partnerships between adult literacy teachers and community health providers to deliver a health literacy training program in adult basic education classrooms. Following course completion we interviewed 19 adult education teachers (15 delivering the health literacy program; 4 delivering standard literacy classes) and four community health providers (CHPs) about their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…This study forms part of a larger program of work evaluating the impact of our adult education health literacy training program. 12,13,[15][16][17][18] Combined, our results add to the growing evidence that adult basic education institutions have potential to develop transferable health literacy skills among socially disadvantaged groups. These qualitative findings further support theories of adult learning, which posit that adult learners are motivated to learn when they understand the relevance of the content to their daily lives.…”
Section: Synthesis Of Findings With Other Researchsupporting
confidence: 68%
See 3 more Smart Citations
“…This study forms part of a larger program of work evaluating the impact of our adult education health literacy training program. 12,13,[15][16][17][18] Combined, our results add to the growing evidence that adult basic education institutions have potential to develop transferable health literacy skills among socially disadvantaged groups. These qualitative findings further support theories of adult learning, which posit that adult learners are motivated to learn when they understand the relevance of the content to their daily lives.…”
Section: Synthesis Of Findings With Other Researchsupporting
confidence: 68%
“…The social support derived from the course was frequently commented on as a positive outcome of participation, and this observation was also made by teachers of the program (reported elsewhere). 13 Importantly, learners reported that they had become more confident in areas that extended beyond performing the targeted health behaviours, such as engaging in LLN activities in class, and interacting with people in their community. Sharing new knowledge with others in their communities was frequently reported; however, language differences remained an important barrier to engaging with the health system (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis focuses on teachers’ reflections on SDM programme components. Data relating to the other components of the health literacy programme are reported elsewhere . While the focus of this article is on teachers’ experience of delivering SDM content within a health literacy programme, quotes from adult learners are incorporated throughout to support teachers’ reflections on subjective learner experiences.…”
Section: Methodsmentioning
confidence: 99%